Lateral movement of vehicles under weak-lane discipline heterogeneous traffic - Mahapatra, Geetimukta (Penerbit UTM Press, 2016)
Safe driving can be achieved by prevention of risky situations which requires the knowledge of the vehicle dynamics and road geometry. The Indian traffic condition is heterogeneous in nature and has weak lane discipline. Hence, vehicles interactions takes place laterally also along with their longitudinal interaction. Vehicles lateral movements (interactions) are quite high due to absence of lane discipline. Therefore, the lateral acceleration of vehicles are an important variable which characterizes the corresponding vehicle dynamics. Several studies have been done by various authors on lateral acceleration in curves, however, lateral movement study of vehicles on straight road section is also important to analyze vehicles’ maneuver in such traffic (i.e. traffic stream with weak lane discipline). Therefore, the present study is about the observation of lateral movements of vehicles over different types of roads in three metropolitan cities of India (Kolkata, Mumbai and Pune) under moderate traffic conditions. Lateral acceleration variation of five different types of vehicles (SUV cars, Sedan cars, Hutch Back cars, motorized three wheeler and two wheeler) have been recorded to investigate its relationship with vehicles longitudinal characteristics (i.e. longitudinal speed) in Indian heterogeneous and weak lane disciplined traffic. Lateral acceleration values quickly rises with initial increase in speed afterward lateral acceleration values reduces with further increase in vehicles longitudinal speed. Impact of vehicle type and locations on the lateral maneuvering of vehicles have also been studied.